The Effect of Taxes on Capital Structure of Companies in Indonesia - Setyawati, Indri; Sunita Firdayana; La Ode Sahlan Zulfadlih; Laode Haksamana; Caca Ardelia; Asriyanti (International Journal of Management and Education in Human Development, 2022)
This study aims to examine the effect of taxes on the company’s capital structure. In particular, the company’s capital structure is proxied by leverage. Proxied by 3, namely: Earning after tax (EAT), Effective tax rate (ETR) and marginal Tax Rate (MTR). The sample in this study were companies listed on the Indonesia Stock Exchange in 2015-2020. The sample was selected using purposive sampling, which consisted of non-financials who implemented a pension program. Tl the analytical method used in this study is panel data regression using Stata software Version 13.0. The results of this study indicate that corporate tax as proxied by Earning After Tax (EAT), effective tax rate (ETR) and Marginal Tax Rate (MTR) has a significant positive effect on the company’s capital structure.